Progressivity of Livestock Policy to Support National Food Security - Syukron, Nurkholis (Jurnal Administrasi Karya Dharma, 2025)
This study examines the progressivity of livestock policies in supporting national food security. Livestock production is a critical component of agricultural economies and plays a significant role in ensuring a stable food supply. Effective policies can enhance productivity, sustainability, and equity within the sector. The objectives of this study are to analyse the transformation of public policy about livestock and to analyse the impact of the new policy about livestock to the citizen life. This research evaluates the impact of various livestock policies implemented across different regions, focusing on their effectiveness in promoting food security. By analyzing policy frameworks, support mechanisms, and their outcomes, the study identifies best practices and potential areas for improvement. Key findings indicate that progressive policies, which integrate sustainable practices, financial support, and access to markets, significantly bolster food security. Additionally, the study highlights the importance of adaptive policies that respond to environmental challenges and evolving market conditions. Recommendations are provided for policymakers to enhance the progressivity of livestock policies, thereby strengthening national food security and ensuring the resilience of the agricultural sector. Keywords : Progresivity, Livestock Policy and Food Security.